Blind Stereoscopic Image Quality Assessment Accounting for Human Monocular Visual Properties and Binocular Interactions - Yun Liu; Weiqing Yan; Zhi Zheng; Baoqing Huang; Hongwei Yu (IEEE Access, 2020)
Human visual perceptual model is a key factor for evaluating stereoscopic image quality. This paper focuses on the contributions of monocular and binocular properties on quality perception and proposes a novel blind stereoscopic image quality assessment model by comprehensively digging the relationship between visual features and quality perception. The statistical quality-aware monocular features are extracted from both left view and right view to reveal monocular quality perception, including the color statistical features which are missed in most previous models, while the multiple features of the summation signal and the entropy features of the difference signal are extracted to quantify the binocular quality perception. Finally, support vector regression (SVR) is utilized to train a regression model based on the extracted features and the subjective scores. Three public databases, LIVE 3D Phase I, LIVE 3D Phase II, and MCL 3D Database, are adopted to prove the effectiveness of the proposed model. Experimental results demonstrate that the proposed model is superior to other existing state-of-the-art quality metrics.